Pubertal developmental, body mass index, and cardiovascular autonomic function in children and adolescents with and without autism spectrum disorder: a four-time point accelerated longitudinal study - Rachael A. Muscatello; Meredith Cola; Simon Vandekar; Blythe A. Corbett (Journal of Neurodevelopmental Disorders)
Abstract Background The Autonomic Nervous System (ANS) regulates ‘automatic’ functions such as heart rate, and alterations may have significant impacts on health outcomes. Cardiovascular measures of autonomic function such as heart rate variability are of interest as biological markers in autism spectrum disorder (ASD). The interplay between the ANS and physical health establishes a need to examine cardiovascular autonomic functioning in youth with and without ASD over development. The current study aimed to identify change in autonomic function and balance across the parasympathetic and sympathetic branches over time as a function of diagnosis, age, pubertal development, and physical health status. Methods The study included 244 ASD (N = 140) or neurotypical (NT) (N = 104) youth, ages 10 to 13 years at enrollment and followed over four years. Resting state autonomic functioning was measured using respiratory sinus arrhythmia (RSA; parasympathetic) and pre-ejection period (PEP; sympathetic). Autonomic balance and regulation were also examined as outcomes. Linear mixed models tested between- and within-group differences in the primary autonomic outcomes as well as the influence of pubertal development, body weight, and medication use. Results Baseline models showed diagnostic differences, with lower parasympathetic regulation, in youth with ASD, but no differences were observed for the other three outcomes. Adding body mass index (BMI) percentile and medication use removed the statistically significant diagnostic effect, while both variables were significantly related to lower RSA and overall autonomic regulation. Parasympathetic function (RSA) was stable over age and pubertal stage, while a notable decrease in sympathetic control (increased PEP) was found for age and pubertal stage. BMI percentile at enrollment significantly predicted autonomic function, while change in BMI over time did not. Conclusions Minimal research to date has explored physical health (e.g., BMI) and autonomic outcomes in ASD. The current study observed few group differences yet demonstrates important effects of physical health on ANS function in both ASD and neurotypical youth. Findings further emphasize a need to focus on individual traits such as BMI and medication use to elucidate the extent to which autonomic differences are related to health status, irrespective of diagnostic category, across the lifespan.